Bridging “Office-Based Care” With the “Virtual Practice Care Model”: Evolving Care for Chronic Kidney Disease Patients in the COVID-19 Pandemic—And Beyond - Zhao, Bingbin; Zhang, Lei; Ji, Peili; Lin, Jianfeng; Han, Jianfang; Li, Jiaying; Zhou, Zijuan; Wang, Haiyun; Qiu, Ling; Hong, Xia; Williams, Winfred; Chen, Limeng (Frontiers in Medicine, 2020)
Since the outbreak of the coronavirus epidemic, the “virtual” telemedicine has become a critical substitute for patient-provider interactions. However, virtual encounters often face challenges in care for high-risk patients such as chronic kidney disease (CKD) patients. In this study, we explore the patient's satisfaction and practical effects of a newly established telemedicine program in CKD patients' care during the pandemic. Based on the previous online patient care platform established in 2017, we improved the procedure, set up the online telemedicine program specific to the COVID-19 pandemic, including triage strategy, medical care delivery, and psychological support, based on a smartphone application. We invited a total of 278 CKD patients to join the new platform during the pandemic. The patients of group A were in our old online CKD system at least three months before the pandemic. A pilot survey interrogating medical and psychological conditions was conducted. The feedback to the program and the psychological assessment repeated after one month. Totally, 181 patients showed active responses to the program, with 289 person-time medical consultations occurred during the study. The virtual care program provided a rapid triage for 17% (30 out of 181) patients, with a timely referral to in-patient medical encounters for their worsening medical conditions or severe psychological problems. Nearly all patients (97.4%) believed the program was helpful. The number of symptoms (OR 1.309, 95%CI 1.113-1.541; P=0.001) and being enrolled during pandemic (OR 3.939, 95% CI 1.174-13.221; P=0.026) were associated with high stress. During the follow-up, the high-stress CKD group at baseline showed a significant decrease in avoidance score (6.9±4.7 vs. 9.8±1.9, P=0.015). In conclusion, during the pandemic, we established an online telemedicine care program for CKD patients that provides a rapid triage function, effective CKD disease management, and potentially essential psychological support.